Literacy Culture in Edutainment Teaching Aids for Early Childhood Education: A Mix Method Study - Iwan Hermawan; Gita Hindrawati; Rina Windiarti; Inayah Inayah (Education Policy and Development, 2025)
The demand for upgrading Teaching Aids increases in line with curriculum developments, especially in the aspect of literacy culture. Teaching Aids is a strategic medium for improving children's literacy skills by bringing the concept of education and entertainment (edutainment) to early childhood. This study aims to explore perceptions of the use of teaching aids that focus on reading corners to develop a literacy culture for ECE children. A holistic perspective was adopted in the study by presenting three perspectives from parents, children, and teachers through a mixed-method approach. Data collection was carried out using random sampling techniques at kindergartens/PAUDs in Indonesia through questionnaire surveys and observations. The findings of this study reveal that an integrative holistic approach strengthens literacy culture as a lifestyle, not just a hobby, and supports the development of students' reasoning and logic. It involves teaching aids from teachers and parental support to create comprehensive character education